2011
DOI: 10.1097/ico.0b013e3181e4570c
|View full text |Cite
|
Sign up to set email alerts
|

Subconjunctival Masses Associated With Central Nervous System Rosai–Dorfman Disease

Abstract: The authors present a case of extensive extranodal involvement of Rosai-Dorfman of the eye and the central nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In this location, adult male predominance was noted; multiple subconjunctival lesions and bilateral affection were commonly accompanied by other nodal and extranodal sites of disease. 7,1328…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this location, adult male predominance was noted; multiple subconjunctival lesions and bilateral affection were commonly accompanied by other nodal and extranodal sites of disease. 7,1328…”
Section: Discussionmentioning
confidence: 99%
“…In this location, adult male predominance was noted; multiple subconjunctival lesions and bilateral affection were commonly accompanied by other nodal and extranodal sites of disease. 7,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Clinical presentation of ophthalmic RDD is non-specific; and it is associated to the site of involvement. The main clinical manifestation in our patients was a painless soft tissue mass causing proptosis in orbit and foreign body sensation when located in conjunctiva.…”
Section: Discussionmentioning
confidence: 99%
“…According to 285 RDD literature reviewed cases [1][2][3][4][5]7,9,10,[12][13][14][15][16][17][18][19][20][21][22][23][24][26][27][28][29][30][31][32][33][34][35][36][37][38][39]41,[44][45][46][47][48][50][51][52][53][54][56][57][58][59][60][61][62]…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, the mass (RDD) extended to the retrobulbar region and has encircled both optic nerves causing compression and complete blindness. Other reported cases have shown that optic nerve compression due to RDD may be unilateral [ 13 , 14 ] or bilateral [ 15 ]. Visual impairment is usually partial [ 15 ].…”
Section: Discussionmentioning
confidence: 99%